Strategien zur Erweiterung der Prozessgrenzen bei der Innenhochdruck-Umformung von Rohren und Blechpaaren - Cojutti, Massimo (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2010)
The aim of this work was the development and validation of innovative process strategies by the hydroforming of tubes and sheet pairs to improve the achievable forming results. The investigations focused on the analysis of the material flow as a key factor for the improvement of the part properties. First the issue of sealing of the fluid by sheet hydroforming was addressed. The results of these investigations were used to improve the technology of hydroforming of tubes and sheet pairs in one tool and manufacture a complex hollow part. Further investigations focused on the development and the validation of a strategy for hydroforming double sheet parts made of inhomogeneous sheet pairs. In this strategy a counterpressure is applied to control the material flow during the proces